Autonomia na aula de português da 3ª etapa da educação de jovens e adultos - GUEDES, Mariza Andrade (Universidade Federal do Pará, 2012)
This research investigated the attitudes of a Portuguese as a native language public school teacher and of her students in a 3rd level EJA class. I searched indications of autonomous behaviors on the part of the teacher and on the part of the pupils as well. I wanted to verify in what measure the teacher transferred responsibility to the learners and how this process occurred. Theor etical basis for this study are found in the work on autonomy of Benson (2001), Dam (2003), Dickinson (1994), Melo (2007), Magno e Silva (2008), and the official documents as the Parâmetros Curriculares Nacionais (1998). Results show a meager worry on the part of the teacher in transferring responsibilities which could eventually lead students to an autonomization process. This study opens the possibility of rethinking classroom practices as a way in which the exercise of autonomy could be possible.